The Sakyadhita Movement - (:unkn) unknown (My University, 2020)
The purpose of this paper is to fill the gap on the scholarship about the global movement to reinstate the higher ordination of women in Buddhism. More specifically, regarding the history of the Sakyadhita International Association of Buddhist Women. There is a history of the Sakyadhita on their website, but it does not include the socio-historical contexts of the movement nor does it contain impactful local events. Much of the outside scholarship focuses on discussing specific issues or topics within the movement as a whole, but none have provided a historical outline on what has happened. This paper intends to work on creating a full historical outline on the history of the Sakyadhita movement. With this, I will also follow what attendees of their conferences say, and how it impacts the global movement. Criticisms of the movement will also be explored, mainly the tension between Western feminists and local communities. I have chosen to do this because the group, Sakyadhita, is a large component in the global movement to reinstate the higher ordination of women. They are the ones who host conferences about the subject, and work with local movements as well. This paper will start around 1988, when the first conference was held, and end as close to the current year as possible. The primary sources that I will be using in this work will mainly be the writings of monks and nuns whose essays are presented at Sakyadhita conferences, and from texts from the Pāli canon. There are issues with some of these primary sources as there are scholarly monks and nuns, but I will narrow a focus to monks and nuns who explicitly argue for (or against) the higher ordination of women by describing what the Buddha would want.